KOMPARASI MEDIA PEMBELAJARAN KOKAMI DAN MEDIA ULAR TANGGA MENGGUNAKAN MODEL PEMBELAJARAN LANGSUNG PADA MATERI STRUKTUR ATOM TERHADAP HASIL BELAJAR SISWA KELAS X SMA NEGERI 5 AMBON - Imarsih Ninkeula; Y T Filindity; Y H Dulanlebit (Molluca Journal of Chemistry Education (MJoCE), 2019)
Comparative study of learning media of mysterious card box with the media of snake ladder on the material of atomic structure to the result of study of class X student of SMA N 5 AMBON. The mysterious card learning media box is applied to the X class MIA1 and the ladder snake media in the X class of MIA3. From the results, the mysterious card learning media box can improve student learning outcomes, seen from the presentation of the achievement of the final test results obtained by the two classes, where the two classes have a presentation of different final result qualification ie qualification completed for class X-MIA1 which uses the mysterious card box learning medium is 100%, and no qualifying fails with an average rating of 85.68. But for the class X-MIA3 using the learning media of snake ladder with qualified thoroughly is 51.51% and qualification failed 48.49% with an average value of 72.95, therefore Mann Whitney test results using SPSS 20 obtained a significance value of 0.002 (> 0.05 ) thus H0 is rejected and H1 is received so it can be concluded that there are differences in student learning outcomes using the mysterious box learning media and learning media snake ladder